Simulation for Enhancement in Sensitivity of Chalcogenide Glasses-Based Fibre Optic Evanescent Absorption Sensor for Malignant Tissue Detection - Singh, Ritesh K.; Mishra, Adarsh Chandra; Lohia, Pooja; Dwivedi, Dilip Kumar (Micro and Nanosystems, 2021)
Background: Refractive index determination of biological tissues is a challenging issue. Many biological species also show vibrational signature in the infrared domain. The chalcogenidebased glasses can be used to make the fibree optic evanescent wave sensors for the detection of the analyte. Objectives: The primary objective is to study the effect of various parameters on the sensitivity of chalcogenide glass-based evanescent-wave sensor for biological tissue detection. Methods: An evanescent wave sensor has been proposed with collimated source illumination and uniform tapering. The chalcogenide materials are chosen such that the weakly guiding approximation could be followed. Complex refractive indices of liver tissue samples have been taken for the analysis of sensitivity via the method of the evanescent absorption coefficient. Equations for sensitivity have been solved analytically using MATLAB software. Results: The simplification of the formula for sensitivity leads to the inference that the sensitivity is a function of core radius, refractive indices of sample tissues and wavelength used. Moreover, since the refractive indices of the materials are also a function of temperature, therefore a change in temperature results in a change in the profile of guiding mode. Hence, the effect of temperature must also be observed. The initial simulation parameters are taken; core radius 100 μm, sensing length 4 cm and wavelength 1.0 μm. In the NIR region, we have a better sensitivity of detection for all the tissue samples and the risk of photodamage of the bio-samples is reduced to a good extent. It has been found that sensitivity decreases with wavelength and core radius, whereas increases with temperature. It has also been shown that sensitivity is found to be better with collimated in comparison with the diffused source. Conclusion: The comparative study results that one should operate at a shorter NIR region of wavelength for higher sensitivity. The collimated source illumination should be preferred over diffused one for launching the light within the fibree to have high sensitivity. Further, the length of the sensing region should be larger, but the fibree core radius should be smaller. The proposed biosensor is robust and can also be used many times if the probe (sensing region) is cleaned properly. Moreover, a small amount of analyte is enough for detection. Thus, the proposed sensor is very useful for biomedical applications with its high performance, accuracy and robustness.
Keywords: refractive index